2018
DOI: 10.1164/rccm.201801-0168ws
|View full text |Cite
|
Sign up to set email alerts
|

Female Sex and Gender in Lung/Sleep Health and Disease. Increased Understanding of Basic Biological, Pathophysiological, and Behavioral Mechanisms Leading to Better Health for Female Patients with Lung Disease

Abstract: Female sex/gender is an undercharacterized variable in studies related to lung development and disease. Notwithstanding, many aspects of lung and sleep biology and pathobiology are impacted by female sex and female reproductive transitions. These may manifest as differential gene expression or peculiar organ development. Some conditions are more prevalent in women, such as asthma and insomnia, or, in the case of lymphangioleiomyomatosis, are seen almost exclusively in women. In other diseases, presentation dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
54
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 87 publications
6
54
0
2
Order By: Relevance
“…In addition, MA challenged mice of all three populations (WT, ERa KO, and ERb KO) showed a significant decline in lung function compared to respective PBS treated mice. Here, female mice exposed to MA in all three study populations showed prominent decline compared to males, which corroborates with clinical data suggesting increased severity of asthma in females (Weiss and Gold, 1995;de Marco et al, 2000;Melgert et al, 2005;Vink et al, 2010;Han et al, 2018). In addition, the severity of MA induced AHR and remodeling was found to be more pronounced in ERb KO mice compared to WT and ERa KO.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, MA challenged mice of all three populations (WT, ERa KO, and ERb KO) showed a significant decline in lung function compared to respective PBS treated mice. Here, female mice exposed to MA in all three study populations showed prominent decline compared to males, which corroborates with clinical data suggesting increased severity of asthma in females (Weiss and Gold, 1995;de Marco et al, 2000;Melgert et al, 2005;Vink et al, 2010;Han et al, 2018). In addition, the severity of MA induced AHR and remodeling was found to be more pronounced in ERb KO mice compared to WT and ERa KO.…”
Section: Discussionsupporting
confidence: 89%
“…Airway mechanics were determined using the forced oscillation technique (FOT) of the FlexiVent Fx1 module, which is an invasive endpoint technique that delivers parameters like airway resistance (Rrs), compliance (Crs), elastance (Ers), tissue elasticity (H) and tissue damping (G), which together depict the overall lung function (Aravamudan et al, 2012;Ambhore et al, 2019a). Our study shows that ERb KO mice show deteriorated lung function compared to WT and ERa KO in both the genders at baseline, with prominent changes observed in females compared to males, which correlates with earlier clinical findings suggesting females are susceptible to asthma (Weiss and Gold, 1995;Angele et al, 2000;de Marco et al, 2000;Caracta, 2003;Melgert et al, 2005;Carey et al, 2007b;Matsubara et al, 2008;Takeda et al, 2013;Han et al, 2018). Interestingly, ERa KO mice of either sex showed no changes in lung function compared to WT mice at baseline, which can be attributed to the protective role of ERb or detrimental role of ERa in the airways, especially in ASM (Ambhore et al, 2018;Ambhore et al, 2019a).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As long as drug trials jci.org hypoxic patients by using a combination of noninvasive ventilatory support devices and patient positioning (20). As there are sex-based differences in lung physiology including airway caliber, lung volumes, diaphragmatic excursion, accessory muscle mechanics, and abdominal fat distribution (21), sex-disaggregated outcome data on different invasive and noninvasive ventilatory modalities are crucial, but have not been included in preliminary studies.…”
Section: Drug Efficacymentioning
confidence: 99%
“…The interesting data reported by MENDELSON et al [11] have been collected from previously published clinical studies and therefore reflect some limitations found commonly in clinical research. Indeed, as it is often seen in cardiovascular and OSA studies [17][18][19][20][21], women and the elderly were under-represented [11]. This limitation is relevant because previous research has shown that the association of OSA with significant reductions in quality of life scores is independent of sleepiness and comorbidities in men less than 69 years old, but not in men older than 70 years [15].…”
mentioning
confidence: 99%